Synthesis, Structure, and Antiproliferative Activity of Three Gallium(III) Azole Complexes - Stergios Zanias; Giannis S. Papaefstathiou; Catherine P. Raptopoulou; Konstantinos T. Papazisis; Vasiliki Vala; Dimitra Zambouli; Alexandros H. Kortsaris; Dimitrios A. Kyriakidis; Theodoros F. Zafiropoulos (Bioinorganic Chemistry and Applications)
As part of our interest into the bioinorganic chemistry of gallium, gallium(III) complexes of the azole ligands 2,1,3-benzothiadiazole (btd), 1,2,3-benzotriazole (btaH), and 1-methyl-4,5-diphenylimidazole (L) have been isolated. Reaction of btaH or btd with GaBr3 or GaCl3 resulted in the mononuclear complexes [GaBr3(btaH)2] (1) and [GaCl3(btd)2] (2), respectively, while treatment of GaCl3 with L resulted in the anionic complex (LH)2[GaCl4] (3). All three complexes were characterized by single-crystal X-ray crystallography and IR spectroscopy, while their antiproliferative activities were investigated against a series of human and mouse cancer cell lines.